2007
DOI: 10.1002/hyp.6816
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical appraisal of ice‐ and rock‐glacier meltwater in the hyperarid Agua Negra drainage basin, Andes of Argentina

Abstract: Abstract:The Agua Negra drainage system (30°12 0 S, 69°50 0 W), in the Argentine Andes holds several ice-and rock-glaciers, which are distributed from 4200 up to 6300 m a.s.l. The geochemical study of meltwaters reveals that ice-glaciers deliver a HCO 3 -Ca 2C solution and rock-glaciers a SO 4 2 -HCO 3 -Ca 2C solution. The site is presumably strongly influenced by sublimation and dry deposition. The main processes supplying solutes to meltwater are sulphide oxidation (i.e. abundant hydrothermal manifestations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…Discharge measurements confirmed that meltwater from areas affected by permafrost conditions and seasonally frozen ground account for an important share of ~20% discharge, which increases up to 30% after snow melt during the ablation season (Schrott, 1994;Schrott, 1996). Hydrochemical analysis of melt water indicates significant internal recycling by sublimation and 120 evaporation and delayed meltwater throughputs from rock glaciers (Lecomte et al, 2008). Geophysical investigations on the El Paso rock glacier suggest that the active layer traps and conducts water and interacts with the permafrost table during summer thaw, while ice-rich permafrost is an important water reservoir releasing water mainly during droughts (Croce and Milana, 2002).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Discharge measurements confirmed that meltwater from areas affected by permafrost conditions and seasonally frozen ground account for an important share of ~20% discharge, which increases up to 30% after snow melt during the ablation season (Schrott, 1994;Schrott, 1996). Hydrochemical analysis of melt water indicates significant internal recycling by sublimation and 120 evaporation and delayed meltwater throughputs from rock glaciers (Lecomte et al, 2008). Geophysical investigations on the El Paso rock glacier suggest that the active layer traps and conducts water and interacts with the permafrost table during summer thaw, while ice-rich permafrost is an important water reservoir releasing water mainly during droughts (Croce and Milana, 2002).…”
Section: Study Sitementioning
confidence: 99%
“…The hydrologic importance of water storage capacities in rock glaciers compared to glaciers (Croce and Milana, 2002;Milana and Maturano, 1999) as well as river discharge (Schrott, 1996) and chemistry during summer months due to the melt of frozen ground (Lecomte et al, 2008) has been previously investigated in the Upper Agua Negra catchment in the dry Andes of Argentina. The present study of the talus rock glacier 'Dos Lenguas' builds upon this earlier research and presents 90 results of high-resolution surface detections and extensive hydro-geophysical subsurface measurements in the data-scarce region of the dry Andes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high TDS concentration, Tunuyán River Na + /Ca 2+ ratios (~0.76) are low for waters exposed to intense evaporation. Moreover, the waters of adjacent basins under equal climatic conditions but in volcanic lithology are diluted (Lecomte et al ., ). The usual represented end‐member for evaporitic rocks influencing the river chemistry is high in salt rock content and therefore is expected to show high Na + /Ca 2+ values (Ollivier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Lecomte et al . () studied the hyperarid Agua Negra Stream basin (~30 ° S, ~4000 m asl), located at 160 km from the ocean. These authors found Na + /Ca 2+ ratios ~2.40 in snow samples and estimated that all Cl − and part of Na + transported by that stream originate from marine aerosols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation